Analyzing the Impact of E-Service Quality and Information Quality on Student Satisfaction: A Case Study at Lemondial Business School - Wati, Mirna; Putranto, Diyan (International Journal of Educational and Life Sciences, 2024)
This study examines the influence of e-service quality and information quality on student satisfaction at Lemondial Business School, focusing on The Genius portal. Utilizing a quantitative approach, data were collected from 80 students through a structured questionnaire. Results indicate significant positive correlations between e-service quality (r = .732) and information quality (r = .785) with student satisfaction. Multiple regression analysis reveals both e-service quality and information quality as significant predictors of student satisfaction, with coefficients of 0.452 and 0.578, respectively. Qualitative insights highlight the importance of responsiveness and accurate information. Recommendations include enhancing staff training, implementing systematic content reviews, and establishing feedback mechanisms to improve digital learning environments. This research contributes to understanding these relationships in an Indonesian higher education context.